Geologic Excursions in Southwestern North America 2019
DOI: 10.1130/2019.0055(13)
|View full text |Cite
|
Sign up to set email alerts
|

Crustal shortening and porphyry copper mineralization in the Laramide arc and superimposed extension: Introduction and themes

Abstract: The Laramide continental arc formed in southwestern North America at about the same time the Sierra Nevadan arc was shutting down, and the Laramide arc was active concurrent with the progress of the Laramide orogeny, from ca. 80 Ma to ca. 45 Ma. East-central Arizona offers an excellent opportunity to explore aspects of tectonics, structural geology, magmatism, and hydrothermal systems in a segment of the Laramide arc that is exceptionally well endowed with porphyry copper deposits. The structure of this region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…2), Fajardo (2015) demonstrated that multiple generations of originally steeply west-dipping curviplanar normal faults progressively tilted the area ~65° E. A similar style of extension has been documented in the Tortilla Mountains (Fig. 1, surrounding areas 1-3) around Romero Wash (Favorito and Seedorff, 2017), Hackberry Wash (Maher et al, 2004;Seedorff et al, 2019a), Kelvin-Riverside (Nickerson et al, 2010), Ray (Barton et al, 2005), and west of Ray near Walnut Canyon (Favorito and Seedorff, 2020). In each of these locales, detailed documentation of crosscutting relations between Cenozoic normal faults and related synextensional strata demonstrate well-defined magnitudes of tilting associated with specific generations of normal faults.…”
Section: Formation Of Catalina Core Complexmentioning
confidence: 64%
See 1 more Smart Citation
“…2), Fajardo (2015) demonstrated that multiple generations of originally steeply west-dipping curviplanar normal faults progressively tilted the area ~65° E. A similar style of extension has been documented in the Tortilla Mountains (Fig. 1, surrounding areas 1-3) around Romero Wash (Favorito and Seedorff, 2017), Hackberry Wash (Maher et al, 2004;Seedorff et al, 2019a), Kelvin-Riverside (Nickerson et al, 2010), Ray (Barton et al, 2005), and west of Ray near Walnut Canyon (Favorito and Seedorff, 2020). In each of these locales, detailed documentation of crosscutting relations between Cenozoic normal faults and related synextensional strata demonstrate well-defined magnitudes of tilting associated with specific generations of normal faults.…”
Section: Formation Of Catalina Core Complexmentioning
confidence: 64%
“…In several areas along the San Pedro Valley, authors have interpreted extension in terms of domino-style block faulting (Barton et al, 2005;Nickerson et al, 2010;Fajardo, 2015;Favorito and Seedorff, 2017;Favorito and Seedorff, 2020). In this interpretation, multiple generations of originally high-angle normal faults have rotated to lower angles and progressively tilted and extended blocks of the upper crust (e.g., Proffett, 1977;Gans and Miller, 1983;Mandl, 1987;Richardson et al, 2019;Seedorff et al, 2019a). Conversely, variations on low-angle detachment and rolling hinge models (e.g., Wernicke, 1981;Buck, 1988;Wernicke and Axen, 1988;Whitney et al, 2013) typically have been used in recent decades to explain intense crustal extension and related ductile tectonic fabrics in the Santa Catalina and Rincon Mountains (Dickinson, 1991; (Favorito and Seedorff, 2017).…”
Section: ■ Introductionmentioning
confidence: 99%
“…This is consistent with paleo-crustal thickness estimates derived from Sr/Y and La/Yb ratios of Laramide granitic rocks 65 and indicates the crust was thinned by a factor of two during subsequent Basin and Range extension. Notably, these findings argue against the traditional premise that Laramide shortening did not result in significant crustal thickening in Arizona 14,15 . We suggest this is because the thrust belt was significantly dismembered by Basin and Range extension and that many of the Laramide thrusts are not easily recognised or appreciated.…”
Section: Tectonic Magmatic and Metallogenic Implicationsmentioning
confidence: 72%
“…73-53 Ma 7,8,13 (Table S1); and (3) contractional structures active between ca. 80-60 Ma 14,15,16 . All these features are concentrated in a series of NW-SE trending belts (the Colorado Plateau Transition Zone, CPTZ; Fig.…”
Section: Flat-slab Subduction and Crustal Anatexis During The Laramid...mentioning
confidence: 99%